A new African species of Stenichnodes (Coleoptera: Staphylinidae: Scydmaeninae) - Jałoszyński, Paweł (Zootaxa, 2019)
The genus Stenichnodes is known to occur in Africa and SE Asia, and is divided into two subgenera. The sole African species belongs to Stenichnodes s. str. and is known from a single male specimen found in Chad. A specimen collected in Kenya that has spent nearly 30 years in a museum collection misidentified as a female of Parastenichnaphes cf. sumatrensis (sic!) is here recognized as a male of Stenichnodes s. str. and described as S. error sp. n.